Strategies to Increase Personal Resilience in Disaster Response Efforts - Amanda D. Ali; Angela Lindsey; Amy Harder; Lisa Lundy; T. Grady Roberts (EDIS)
In 2018, Hurricane Michael caused extensive damage in the Florida panhandle as a Category 4 hurricane. Cooperative Extension has a disaster preparedness and information dissemination role in hurricane response (Medford-Davis & Kapur, 2014; Washburn, 2006). Personal resilience focuses on reducing stress and increasing coping abilities in stressful situations. A basic qualitative research design explored UF/IFAS Extension agents’ hurricane experiences. Results suggested participants experienced some inability to balance personal and professional demands and were mentally and emotionally stressed. Participants felt fatigued and results suggested they experienced high levels of mental and emotional stress. There is scope to improve Extension agents’ personal resilience by: (1) strengthening individual levels of hardy attitudes and hardy strategies; and (2) reducing barriers such as mental and physical stress and performance deficits.